2021
DOI: 10.3390/molecules26061548
|View full text |Cite
|
Sign up to set email alerts
|

Green Synthesis of Nickel Oxide Nanoparticles from Berberis balochistanica Stem for Investigating Bioactivities

Abstract: Green synthesis of nanomaterials is advancing due to its ease of synthesis, inexpensiveness, nontoxicity and renewability. In the present study, an eco-friendly biogenic method was developed for the green synthesis of nickel oxide nanoparticles (NiONPs) using phytochemically rich Berberis balochistanica stem (BBS) extract. The BBS extract was rich in phenolics, flavonoids and berberine. These phytochemicals successfully reduced and stabilised the NiNO3 (green) into NiONPs (greenish-gray). BBS-NiONPs were confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
37
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 71 publications
(45 citation statements)
references
References 41 publications
2
37
1
Order By: Relevance
“…In comparison with the standard drug doxycycline, the bark extract showed significant effectiveness against both Gram-positive and Gram-negative bacteria, followed by the leaf and root extracts (Figure 1). The results of the current study were in agreement with those previously reported (Uddin et al, 2021) and relatively higher than those found in the literature (Kakar et al, 2012). However, Pervez et al (2019) evaluated the antibacterial potential of berberisinol that exhibited a significant activity against E. coli, S. aureus, and S. pyogenes, a moderate activity against B. subtilis and K. pneumoniae, and a weak activity against P. aeruginosa.…”
Section: Discussionsupporting
confidence: 94%
“…In comparison with the standard drug doxycycline, the bark extract showed significant effectiveness against both Gram-positive and Gram-negative bacteria, followed by the leaf and root extracts (Figure 1). The results of the current study were in agreement with those previously reported (Uddin et al, 2021) and relatively higher than those found in the literature (Kakar et al, 2012). However, Pervez et al (2019) evaluated the antibacterial potential of berberisinol that exhibited a significant activity against E. coli, S. aureus, and S. pyogenes, a moderate activity against B. subtilis and K. pneumoniae, and a weak activity against P. aeruginosa.…”
Section: Discussionsupporting
confidence: 94%
“…Plant materials and products have abundant amounts of these antioxidant compounds ( Iqbal et al, 2018a , Iqbal et al, 2018b , Iqbal et al, 2018c ). Many plant-containing phytochemicals have been used in the treatment of hepatic and renal diseases, either given independently or collectively ( Karakuş et al, 2017 , Usman et al, 2020 , Hameed et al, 2021 , Uddin et al, 2021 ). Two such phytochemical-rich and antioxidant-rich medicinal plants reported for their significant antioxidant, anti-inflammatory, hepatoprotective ( Ali et al, 2017 , Ali et al, 2018b ), antimicrobial ( Ali et al, 2018a , Ullah et al, 2015 ), anticancer and wound healing ( Ali et al, 2021c , Ali et al, 2021d ) potential is Parrotiopsis jacquemontiana (Decne) Rehder and Periploca hydaspidis Falc.…”
Section: Introductionmentioning
confidence: 99%
“…Utilization of therapeutic spices as antiquated prescription is one of the consistently utilized practices in subcontinent. Plants have consistently been a wellspring of fix to various infections because of essence of numerous phytochemical compounds [1]. Medications that are acquired from home grown sources have a striking impact in forestalling and relieving deadly illnesses.…”
Section: Introductionmentioning
confidence: 99%